Citizenship in heaven and on earth: Karl Barth's ethics - Maßmann, Alexander (Fortress Press, 2015)
The development of Barth's ethics from the First Epistle to the Romans to Church Dogmatics I/1 -- The ethics of the doctrine of God in Church Dogmatics II/2 -- The ethics of the doctrine of creation in Church Dogmatics III/4 -- The foundations of ethics in the doctrine of reconciliation in Church Dogmatics IV -- Perspectives: responsibility and faith in the Triune God